Метод розроблення специфікацій та вимог в процесі реінжинірингу ІТ-проектів - Керницький, О. Б.; Теслюк, В. М.; Kernytskyy, O. B.; Teslyuk, V. M. (Видавництво Львівської політехніки, 2023)
У даному дослідженні метою є вдосконалення методу синтезу вимог та специфікацій для реінжинірингу ІТ-проектів з максимальною ефективністю та бізнес-орієнтованістю. Основним завданням є адаптація застарілих ІТ-систем до змінюваного технічного середовища, зокрема до хмарних технологій та вимог до систем безпеки. Для досягнення цих цілей, запропонована методу використовує аналіз архаїчних систем, метод зворотної розробки, опитування експертів, аналіз документації та моделювання чорного ящика. Застосування цих методів дає змогу виявити та коригувати вимоги та специфікації, забезпечуючи високий рівень якості та ефективності у процесі реінжинірингу ІТ-проектів. У статті далі розглядаються практичні використання методу, перспективи подальшого розвитку та особливості застосування різних статистичних методів у процесі покращення результатів реінжинірингу. Описуються принципи роботи методу разом із основними підходами та техніками, які сприяють аналізу існуючих ІТ-систем, синтезу вимог та специфікацій, контролю якості та ефективності реалізації проектів реінжинірингу. Окремо проаналізовані складові методу містять збір даних про існуючу систему та здійснення аналізу архаїчних систем з метою визначення вимог до нової системи. Розглядається застосування моделі чорного ящика для тестування розробленої системи, включаючи аналіз отриманих результатів, коректування вимог та покращення специфікацій. Метод включає засоби аналізу документації, реверсивного інжинірингу, опитувань і відображення даних, а також методики аналізу, наприклад формулу паралельного тестування, формулу матриці відповідності вимог та формулу прогнозування вимог на основі аналізу швидкості розбіжностей.

In this study, the aim is to create and improve a methodology for synthesizing requirements and specifications for the re-engineering of IT projects with maximum efficiency and business orientation. The main task is to adapt outdated IT systems to the changing technical environment, in particular to cloud technologies and security system requirements. To achieve these goals, the proposed methodology uses the analysis of archaic systems, the reverse engineering method, expert surveys, documentation analysis, and black-box modeling. The application of these methods allows for the identification and revision of requirements and specifications, ensuring a high level of quality and efficiency in the process of re-engineering IT projects. The article further discusses the practical aspects of applying the methodology, prospects for further development, and the peculiarities of using various statistical methods in the process of improving re-engineering results. The operating principles of the method are described along with the main approaches and techniques that promote the analysis of existing IT systems, the synthesis of requirements and specifications, quality control, and successful project implementation. The individual components of the method include the collection of data about the existing system and the analysis of archaic systems to restore the definition of requirements. The use of the black-box model for testing the developed system is discussed, including the analysis of the obtained results, correction of requirements, and improvement of specifications. The methodology includes documentation analysis tools, reverse engineering, surveys and data visualization tools, as well as analytical techniques such as a formula for parallel testing, a formula for requirement traceability matrix, and a formula for forecasting requirements based on discrepancy rate analysis. As a result of implementing the IT project reengineering method, successful transition from old to new technologies can be achieved, the IT industry can be optimized, and conditions can be created for adaptation to modern technical environments, ensuring stability and reliability of the implemented reengineering projects. Based on the analysis of modern sources, previous experience, and conducted research, it can be asserted that the method for synthesizing specifications and requirements in the process of reengineering IT projects is of great importance and relevance for the modern development of information technology and business processes.
The synthesis method for specifications and requirements in the process of it project reengineer-ing
Keywords: реінжиніринг ІТ-проектів; архаїчні системи; паралельне тестування; модель чорного ящика; матриця трасування вимог; хмарні технології; IT project reengineering; Archaic systems; Parallel testing; Requirement Traceability Matrix; Discrepancy rate analysis; Cloud technologies; 004.4